Introduzione alle antichità di Ventotene : ricerche archeologiche nell'isola di Ventotene 1 - De Rossi, Giovanni Maria; Medaglia, Salvatore, 1971- (Ricerche archeologiche nell'isola di Ventotene, 2018)
Ventotene, a small island located in the Tyrrhenian sea, hosts the ruins of a large Roman villa dated to the Augustan age where many women related to imperial families were exiled and enclosed. This volume offers an introduction to the Roman antiquities of Ventotene and is the first of a series of thematic monographs dedicated to the island.